International map of the world 1:1 000 000. SI 51,. Esperance Carte internationale du monde 1:1 000 000. - Australia. Division of National Mapping (Canberra : NATMAP, 1980)
Map is a part of a world topographic series.
English text, parallel French translation.
Keywords: Esperance (W.A.) -- Maps; Topographic maps